Socio-cultural factors affecting maternal health system in District Buner, Khyber Pakhtunkhwa Pakistan - Wahab, Pir; Badshah, Saddam; Ud Din, Shams; Pasha, Kinan (Masyarakat, Kebudayaan dan Politik, 2023)
The primary objective of this study was to investigate the underlying social and cultural determinants that influence the utilization of child delivery services in the Buner district, located in Khyber Pakhtunkhwa. The research focused on a specific demographic group, namely pregnant women and their husbands aged between 15 and 49 years. A sample of 200 participants was selected using a multistage sampling technique, and data was collected through structured questionnaires employing mixed methods. Data analysis was conducted using SPSS, utilizing statistical tools like frequency distribution tables for univariate analysis and the chi-square test for bivariate analysis. The study showed a strong connection between socio-cultural factors and the child delivery system, with evident implications for the maternal health framework. The results of the chi-square test highlighted the strength of this association, as the calculated value (190.627) was significantly greater than the tabulated value (9.488) at a significance level of 0.05. The research highlights the impact of socio-demographic factors, including cultural barriers, extended family structures, and economic disparities, on maternal health services and their relationship with the utilization of antenatal care services. To improve the situation, it is important to focus on improving education, raising awareness, promoting women's empowerment, addressing socioeconomic disparities, and transforming traditional beliefs prevalent within the local community.